Influence Of Light Emitting Diodes On Dendrobium Hybrid Orchid Plantlets - Yeow, Lit Chow (2021)
The long juvenile stage and slow growth rate of orchids make their vegetative propagation to be time consuming and labour-intensive. In this context, micropropagation serves as an eminent approach for large scale production of genetically identical orchid plantlets within a short time. The engagement of light-emitting diode (LED) permits the adjustment of light profile and aids in fostering growth and development of in vitro cultures, as narrow light spectrum is anticipated to induce photomorphogenesis. The present study aimed to promote the growth of a Dendrobium orchid hybrid (Dendrobium Enopi x Dendrobium Pink Lady) through micropropagation means.